Investigación de las necesidades de formación y expectativas de las empresas de Itapúa (Journal on studies and research of academic knowledge, 2011)
We have investigated the needs of short  and post graduate courses of companies in  the Department of Itapúa  for their staff and their expectations,  specifically on new careers required by them or their community, their willingness to join an electronic employment exchange via Internet as a source of recruitment, which would contain the resumés of students and graduates of the UNI, the predisposition of the surveyed companies to enable a common forum or joint commission between the university and themselves and finally as a complement  if they have already contracted UNI  graduates, we have asked about their level of satisfaction. The academic areas of the surveys have covered the faculties of economics, agricultural engineering, civil engineering, electromechanical engineering and computer engineering. The research corresponds to a nonexperimental descriptive design. There is data, information and results of a representative sample of the population of companies listed as contributors to the Ministry of Finance, in all cases, legal persons (corporations, limited liability companies, cooperatives and public agencies or governmental offices in the department). The results have allowed to know what short courses (open to the general public) are needed to the staff in the companies surveyed, as well as what post graduate courses are most required from the academic areas mentioned above. The results have also shown very important information for the analysis and decisions that the institution could take to address currently unmet demand, with a range of possible really interesting courses, that apart from being properly managed could become an interesting source of new revenue for the university. In addition, consultations on a joint commission, board or common space to manage new projects such as electronic job bag, or a business incubator, among others, have had promising results in terms of the willingness of companies.
Keywords: training; needs; companies